Strengthening Early Intervention Ecosystems in Rural Assam: Evidence from Goalpara and Karbi Anglong Districts - Saddam Hussain; Dr. Koona Lalitha (Revista Electronica de Veterinaria, 2024)
Background: Early Intervention (EI) programs provide aid to children from zero to six years old who have disabilities or experience some delays in the areas of cognitive, motor, language, and socio-emotional development. Inaccessibility to Early Intervention programs is a problem in the rural areas of the North-Eastern region of India in connection with poor infrastructure, lack of awareness among community members, socio-economic factors, lack of professionals, and cultural barriers. Objectives: The present study aims to analyse obstacles to the accessibility of Early Intervention Programs in rural areas of Rangjuli Block of Goalpara District, and Manja Block of Karbi Anglong District of Assam, and suggest measures to develop early intervention programs in such areas. Methods: A qualitative review approach and contextual field analysis were chosen for data synthesis based on the literature and research findings. Relevant studies and policies relating to disabilities and early intervention were reviewed for information about various challenges and proposed solutions for better access to EI programs. Findings: The study reveals that the inadequate infrastructure, poor socio-economic status, and cultural stigmatization negatively affect the access and acceptance of the EI service. Community-based rehabilitation, intersectoral coordination, training of frontline workers, and engagement of families through culturally sensitive approaches became the key approaches for strengthening the EI program. Conclusion: This study underscores the importance of developing sustainable and inclusive EI interventions in rural areas. The promotion of coordinated action involving various sectors can contribute to improved developmental outcomes in children living in rural Assam.